Profile of Students' Critical Thinking Ability: Implementation of E-Modul Based On Problem-Based Learning - Siti Mahmudah; Tjandra Kirana; Yuni Sri Rahayu (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
Electronic module (E-module) that is based on a problem-based learning science is a teaching material made by being operated online that is simple, flexible and independent, so as to facilitate students' critical ability to solve problems in everyday life and meet global challenges that can be accessed online through certain sites. The use of this E-module supports the digital literacy movement as one of the needs of the 21st century. One of the 21st century abilities that can be trained through the use of E-Modules is critical thinking. This study aims to determine students' critical thinking ability after using E-Modules based on “problem-based learning”. Method used is one shot case study. The results showed that 61.129% of students have very high critical thinking ability, 35.48% of students have high critical thinking ability, and 3.22% of students have moderate critical thinking ability. It shows the use of problem-based learning-based E-Modules is effective in training students' critical thinking ability.